DETERMINAN RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI LQ 45 PERIODE 2017-2021 - Devara, Gavriel Dean Melvin; Winarto, Jacinta (Jurnal Keuangan dan Bisnis, 2023)
The aim of this research is to find the determination of the Current Ratio (CR), Debt to Assets Ratio (DAR) and Return on Assets Ratio (ROA) on stock returns in companies included in the LQ45 list for the 2017-2021 period. The research sample was 21 companies with the following criteria: Companies that are consistently in the LQ45 index for the 2017-2021 period and have complete financial reports, excluding companies in the financial sector. Purposive sampling technique is used in the sampling technique. The analytical method used in this research is multiple linear regression with a significance level of 5%. The F test results of this research state that simultaneously they have a significant effect on stock returns. The results of the t test state that the Current Ratio and Debt to Assets Ratio have a significant negative effect on stock returns, while Return on Assets has no significant effect on the company's stock returns.